Human iPSC‐Vascular smooth muscle cell spheroids demonstrate size‐dependent alterations in cellular viability and secretory function. Issue 11 (11th July 2022) - Islam, Sara; Parker, Jackson; Dash, Biraja C.; Hsia, Henry C.
Abstract: Human‐induced pluripotent stem cells (hiPSC) and their differentiated vascular cells have been revolutionizing the field of regenerative wound healing. These cells are shown to be rejuvenated with immense potentials in secreting paracrine factors. Recently, hiPSC‐derived vascular smooth muscle cells (hiPSC‐VSMC) have shown regenerative wound healing ability via their paracrine secretion. The quest to modulate the secretory function of these hiPSC‐VSMC is an ongoing effort and involves the use of both biochemical and biophysical stimuli. This study explores the development and optimization of a reproducible, inexpensive protocol to form hiPSC‐VSMC derived spheroids to investigate the implications of spheroid size on viability and paracrine secretion. Our data show the successful formation of different sizes of spheroids using various amount of hiPSC‐VSMC. The hiPSC‐VSMC spheroids formed with 10, 000 cells strike an ideal balance between overall cell health and maximal paracrine secretion. The conditioned medium from these spheroids was found to be bioactive in enhancing human dermal fibroblast cell proliferation and migration. This research will inform future studies on the optimal spheroid size for regenerative wound healing applications.